1972
DOI: 10.1111/j.1749-6632.1972.tb16296.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐function Studies in the Bernard‐soulier Syndrome*

Abstract: Summary Studies of platelet function in four kindreds affected with the Bernard‐Soulier Syndrome are summarized. Platelet aggregation induced by ADP and by dilute collagen suspensions was normal, but the increase in optical density and platelet “volume” that normally proceeds aggregation was lacking. Platelet aggregation by bovine fibrinogen was totally deficient, and the rate of aggregation by both ADP and collagen was abnormally rapid. The serum prothrombin time was abnormal, but other tests of platelet fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 27 publications
4
30
0
Order By: Relevance
“…Platelets from patients with Bernard-Soulier syndrome have less sialic acid than normal (35), and these platelets are not aggregated by bovine fibrinogen (10) or by purified bovine Factor VIII (11), suggesting that sialic acid might play a role in the aggregation of platelets by Factor VIII. However, we found that 60% of the sialic acid could be removed from formalintreated platelets without inhibiting the agglutination by bovine Factor VIII.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets from patients with Bernard-Soulier syndrome have less sialic acid than normal (35), and these platelets are not aggregated by bovine fibrinogen (10) or by purified bovine Factor VIII (11), suggesting that sialic acid might play a role in the aggregation of platelets by Factor VIII. However, we found that 60% of the sialic acid could be removed from formalintreated platelets without inhibiting the agglutination by bovine Factor VIII.…”
Section: Resultsmentioning
confidence: 99%
“…Aggregation can be restored by the addition of purified human Factor VIII (9), but not by other plasma components. Platelets from patients with Bernard-Soulier syndrome are not aggregated by ristocetin (10) or by bovine Factor VIII (11).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine von Willebrand factor, the active agent in bovine fibrinogen preparations (30,31), agglutinates normal but not Bernard-Soulier platelets (32). Agglutination by bovine von Willebrand factor has many features in common with agglutination by the combination of human von Willebrand and ristocetin (8,(10)(11)(12)(13)).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have suggested that the bleeding tendency arises from an abnormality in the platelet-vessel wall interaction, or more specifically, in a diminished platelet ability to adhere to subendothelium (2)(3)(4). B-S platelets are not agglutinated by bovine factor VIII (5,6) or by ristocetin in the presence of normal human plasma (7,8). A diminished binding of certain coagulation factors to B-S platelets has been noted (6) whereas a reduced binding of 125I-labeled thrombin to B-S platelets was correlated with a decreased aggregation response specifically observed with this stimulus (9,10).…”
Section: Introductionmentioning
confidence: 98%